Promotion Strategy of @hobimakan_garut Instagram Account to Increase Sales - Zikri, Zikri Fachrul Nurhadi; Haryadi Mujianto; Syalsa Syabila Putri (LPPM Stikosa - AWS, 2024)
This research is motivated by the large amount of competition in the culinary business, this competition makes business people compete to carry out promotions in various ways, one of which is using the social media Instagram. There are still many culinary business actors who have not used or utilized social media properly and correctly. The aim of this research is to explain the promotional strategy carried out by @hobimakan_garut in promoting culinary delights using the Marketing Mix 4C Context, Communication, Collaboration and Connection approach. The research method used in this research is a descriptive method with a qualitative approach. Data collection techniques use in-depth interviews, literature study, documentation and observation. The subjects in this research were business actors who had promoted the Instagram account @hobimakan_garut, totaling 2 business actors and 3 managers @hobimakan_garut. The research results show that aspects of the Context approach always pay attention to managing language structure, conveying information, characteristics and clarity in every content posted through a photo or video. In Communication @hobimakan_garut utilizes various features to communicate with followers, such as feeds, reels, comments columns, direct messages, insta stories, Instagram live and question boxes. Collaboration applies the tagline